2012
DOI: 10.1002/masy.201000096
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Assessment of PE 80 and PE 100 Pipe Lifetime Based on Paris‐Erdogan Equation

Abstract: Summary: A novel accelerated fracture mechanics extrapolation procedure based on cyclic test with cracked round bar (CRB) specimens was verified by a correlation of real pipe failure time to simulated failure times at a temperature of 60 °C. The procedure was applied to predict the long‐term failure of modern PE 80 and PE 100 pipes 23 °C. Moreover, the used stress intensity factor concept also allows to consider the impact of arbitrary additional loading situations like soil loads or point loads and to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Lifetime of the homogenous pipe in this case is realistic and corresponds well with simulations of the lifetime published [4,30]. The effect of the weld bead is slightly positive in both modes of failure by the axial crack and by the circumferential crack as well.…”
Section: Lifetime Predictionmentioning
confidence: 51%
See 1 more Smart Citation
“…Lifetime of the homogenous pipe in this case is realistic and corresponds well with simulations of the lifetime published [4,30]. The effect of the weld bead is slightly positive in both modes of failure by the axial crack and by the circumferential crack as well.…”
Section: Lifetime Predictionmentioning
confidence: 51%
“…In case of the polymer weld, due to the weld bead development a typical defect size increases and values higher than would be relevant. Material properties of PE 100 were estimated experimentally by Frank et al[30] ( and ). It is shown that the resulting lifetime is strongly sensitive to the initial defect size ( ) and a small increase in the defect size dramatically decreases the lifetime of the structure, see the difference in Figs 26,…”
mentioning
confidence: 99%
“…[6,17] Inspired by these excellent results, the method was adopted to determine fracture characteristics for other materials that are not linear elastic and isotropic, such as bone [18][19][20][21] and polymers, including reinforced [22,23] and nonreinforced thermoplastics, [24], which includes ultra-high molecular weight polyethylene [25,26] and polyethylene pipe grades. [27][28][29][30] It is not trivial to apply a method developed for linear elastic behaviour on non-linear, time dependent materials where the (apparent) modulus strongly depends on loading conditions and loading time. Modifications of the method were, therefore, proposed; e.g.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…For many polymer systems, both glassy and semicrystalline, unfilled and fiber reinforced, it has been demonstrated that, at the same value of the maximum load, application of a high amplitude cyclic load will promote crack‐growth and drastically reduce the failure time compared to that observed in static loading . In the case of polymers with a very high resistance to crack growth, it is, nevertheless, not uncommon that crack‐growth dominated failure is not observed during characterization experiments; a prime example being the absence of crack‐growth dominated failure in current polyethylene (PE) pipe grades during certification testing . The fact that crack‐growth dominated failure is not observed during static tests of over a year only implies that the material is very crack resistant; it will definitely appear at lower loads and longer loading times.…”
Section: Introductionmentioning
confidence: 99%